History Education as an Effort to Internalize Civic Knowledge: A Case Study at an Islamic-Based Private Senior High School in Malang City - Shorunnuha, Inti; Widiadi, Aditya Nugroho; Hudiyanto, R. Reza (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This research aims to understand the process and efforts of internalizing civic knowledge (wawasan kebangsaan) in history learning, identify emerging obstacles, and evaluate the implications of such internalization. This study employs a descriptive qualitative approach. Data collection was carried out through observation, interviews, and documentation. This research data was analyzed using Miles and Huberman’s descriptive data analysis. The findings of the study indicate that: (1) the process of history learning that internalizes civic knowledge involves a series of planning, implementation, and evaluation activities; (2) teachers undergo a series of processes for internalizing civic knowledge, such as value transformation, value transaction, and trans-internalization of values; (3) obstacles and solutions for internalizing civic knowledge through history learning can be seen from the factors of the teachers themselves, the learners, and the implementation of the learning process; (4) the internalization of civic knowledge through history learning has a greater impact on national understanding compared to national pride and national attitudes.